(untitled) (ARQUISUR Revista, 2025)
This article develops a methodology for analyzing images produced by architects to communicate project ideas. The analysis is performed by translating the hermeneutic tools inherent to rhetoric into the field of architectural graphical representation. The first part of our work, thus, includes a summary of the main characteristics of both classical rhetoric (whose systematization was started by Aristoteles in the 4th century B.C.) and neo-rhetorics related to communication through images (developed by Roland Barthes, among others, by the mid-20th century). In the second part, a case ‒an architectural image‒ is deeply studied using the tools defined in the first part (elements, stages, and some of the figures of classical rhetoric). The study concludes that such image can be understood as a graphic discourse, since it represents an elaborate piece of communication of arguments about an architectural project.